2016
DOI: 10.1017/s0144686x16000556
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying the third age! Discourse, identity and liminality in extra-care communities

Abstract: Extra-care housing has been an important and growing element of housing and care for older people in the United Kingdom since the s. Previous studies have examined specific features and programmes within extra-care locations, but few have studied how residents negotiate social life and identity. Those that have, have noted that while extra care brings many health-related and social benefits, extra-care communities can also be difficult affective terrain. Given that many residents are now 'ageing in place' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
(39 reference statements)
1
30
0
Order By: Relevance
“…She said that these residents "don't take part … we don't get any new faces because they seem to want to stay in their flats." Similar findings have been highlighted in other studies (see West et al, 2017).…”
Section: The Changing MIX Of Residentssupporting
confidence: 93%
See 2 more Smart Citations
“…She said that these residents "don't take part … we don't get any new faces because they seem to want to stay in their flats." Similar findings have been highlighted in other studies (see West et al, 2017).…”
Section: The Changing MIX Of Residentssupporting
confidence: 93%
“…In common with previous research on ECH (Callaghan, Netten, & Darton, 2009;West, Shaw, Hagger, & Holland, 2017), the changing mixture of residents living in ECH was a topic that most participants talked about. Many of the participants at sites A, B and D thought that new residents were moving into ECH with higher and more complex needs than they had done previously.…”
Section: The Changing MIX Of Residentsmentioning
confidence: 52%
See 1 more Smart Citation
“…The financial and demographic pressures facing local authorities have, in some areas (including Area 1), resulted in changes to the eligibility criteria for publicly funded ECH, directly impacting the nature of care needs among ECH populations (Skills for Care, ; West, Shaw, Hagger, & Holland, ). The increasing prevalence of those living with dementia places additional demands on the organisation of care.…”
Section: Discussionmentioning
confidence: 99%
“…Under the weight of such socio-cultural expectations of individual identity-and riskmanagement, there are no guarantees that age-segregated communities are any less 'age-denying spatial orders' (Katz and McHugh 2010: 271) than age-integrated environments as authors such as Katz and McHugh (2010) and Blaikie (1999) have observed in the context of North American retirement communities and others in the context of Extra Care retirement communities in the UK (Biggs et al 2000;West et al 2016).…”
Section: Senior Co-housing As a Window On Post-traditional Ageingmentioning
confidence: 99%